2009
DOI: 10.1145/1577755.1577757
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of body shape on the perception of emotion

Abstract: In order to analyze the emotional content of motions portrayed by different characters, we created real and virtual replicas of an actor exhibiting six basic emotions: sadness, happiness, surprise, fear, anger, and disgust. In addition to the video of the real actor, his actions were applied to five virtual body shapes: a low-and high-resolution virtual counterpart, a cartoon-like character, a wooden mannequin, and a zombie-like character (Figures 1 and 2). In a point light condition, we also tested whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…We found that theatrical gestures can be globally considered more skilled, meaningful and elaborated gestures compared to everyday life actions. We also established that for the selected theatrical scenario, emotional states can be successfully elicited in the laboratory setting, and most importantly that our recognition results are very close to those of previous studies in which archetypal affective actions and more complete visual clues were used [15].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We found that theatrical gestures can be globally considered more skilled, meaningful and elaborated gestures compared to everyday life actions. We also established that for the selected theatrical scenario, emotional states can be successfully elicited in the laboratory setting, and most importantly that our recognition results are very close to those of previous studies in which archetypal affective actions and more complete visual clues were used [15].…”
Section: Discussionsupporting
confidence: 83%
“…We chose this kind of representation as we did not want to convey any additional information about the avatar's gender and appearance that might influence the categorization of the selected emotions. Additionally, previous studies have shown that this type of representation does not stop observers from perceiving any emotional state at any intensity [1], [15].…”
Section: Stimuli Creationmentioning
confidence: 80%
“…For computer graphics applications and animations, it is important to consider how observers perceive human characters. As a designer of human characters, it is important to understand how changes in appearance and motion influence the desired perceived attributes of the character [McDonnell 2012;McDonnell et al 2009;Hoyet et al 2010;Kiiski et al 2013]. Our motivation is to gain a greater understanding of the perception of human characters with regard to perceptual attributes when both shape and motion are altered in a systematic way.…”
Section: Introductionmentioning
confidence: 99%
“…The work presented by Neff and Fiume (2006), which focused on the modifications made to the inverse kinematics algorithms to generate different poses to modify the expressiveness of a stance, is also interesting. Finally, the results obtained by McDonnell et al (2008McDonnell et al ( , 2009) are important to our work. They studied the relation between the perception of emotion in virtual characters and their shape and visual aspects, concluding that they are independent of each other.…”
mentioning
confidence: 85%